Prediction of post-induction hypotension in young adults using ultrasound-derived inferior vena cava parameters: An observational study - Sadik Mohammed (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Inferior vena cava (IVC) diameter and its respiratory variability have been shown to predict post-induction hypotension with high specificity in a mixed population of patients. We assessed whether these parameters could be as reliable in healthy adult patients as in a mixed patient population. Methods: In the present prospective observational study, 110 patients of either sex, aged between 18 and 50 years, belonging to American Society of Anesthesiologists class I and II, fasted as per the institutional protocol and scheduled for elective surgery under general anaesthesia were enroled. Prior to induction, ultrasound examination of IVC was done and variation in IVC diameter with respiration was assessed. Maximum and minimum IVC diameters [(dIVCmax) and (dIVCmin), respectively] over a single respiratory cycle were measured and collapsibility index (CI) was calculated. Vitals were recorded just before induction and at every minute after induction for 10 min. Episodes of hypotension (mean arterial pressure [MAP] <65 mmHg or fall in MAP >30% from baseline) during the observation period were recorded. The receiver operating characteristic (ROC) curve was constructed for determining optimum cut-off with sensitivity and specificity of IVC diameters and CI for development of hypotension. Results: IVC was not visualised in 22 patients. Out of the remaining 88 patients, 17 (19.3%) patients developed hypotension after induction. The dIVCmax, dIVCmin and CI were comparable between patients who developed and who did not develop hypotension. The area under curve of ROC for CI, dIVCmax and dIVCmin was 0.51, 0.55 and 0.52, respectively, with optimum cut-off value of 0.46, 1.42 and 0.73, respectively. Conclusion: Ultrasound-derived IVC parameters demonstrate poor diagnostic accuracy for prediction of hypotension after induction in healthy adult patients.